2015
DOI: 10.1017/s1754470x15000598
|View full text |Cite
|
Sign up to set email alerts
|

Service user and clinician perspectives on the use of outcome measures in psychological therapy

Abstract: Abstract. While the benefits of routine outcome measurement have been extolled and to some degree researched, it is surprising that service user opinions on this common therapy practice have largely not been investigated. This study aimed to assess service users' experiences of completing measures during psychological therapy, with a view to exploring how therapists can maximize how helpful measures are in therapy. Fifteen participants completed surveys about the use of measures in their current episode of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Interestingly, the findings indicated that there was a trend towards stronger positive beliefs in both those who do and do not currently use this practice. These findings fit with recent research (Thew et al 2015) in secondary care adult mental health services which found that clinicians generally endorsed positive beliefs about measures more strongly than negative ones.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the findings indicated that there was a trend towards stronger positive beliefs in both those who do and do not currently use this practice. These findings fit with recent research (Thew et al 2015) in secondary care adult mental health services which found that clinicians generally endorsed positive beliefs about measures more strongly than negative ones.…”
Section: Discussionsupporting
confidence: 91%
“…Only one previous study (Moran et al 2012) has explored this, highlighting the importance of their involvement in the process of outcome measurement. Similarly, recent research in adult services (Thew et al 2015) has suggested that service users perceptions of how well measures were used and integrated into therapy were strongly associated with how helpful they found measures as part of therapy overall. Future research further exploring young people's views of session-by-session ROM, the acceptability of this clinical practice and individual measures, and service user experience in relation to clinician's beliefs will be of value.…”
Section: Discussionmentioning
confidence: 89%
“…OCD-experts reported using measures of beliefs, such as the RAS and RIQ (Salkovskis et al, 2000), whereas non-OCD-expert clinicians reported using the OCI (Foa et al ., 1998) to measure outcome. Several studies report that service users find completing questionnaires helpful when their responses were discussed in therapy and felt this strengthened the therapeutic relationship (Lambert et al ., 2002; Unsworth et al ., 2012; Thew et al ., 2015). There is also some evidence that questionnaire use can improve identification of psychological difficulties (Greenhalgh and Meadows, 1999) and potentially improve therapeutic outcomes (Lambert et al ., 2001, 2003; Hawkins et al ., 2004; Harmon et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…First, it is important not to presume that ROM will be a burden for clients as there is evidence that they support the use of measures provided they see practitioners using the information (Thew et al, 2015). And for practitioners, having a positive attitude towards the use of ROM is related to it being a success (Rye et al, 2019).…”
Section: Themementioning
confidence: 99%